2021
DOI: 10.3389/fmicb.2021.728989
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of Staphylococcus aureus to the Human Skin Environment Identified Using an ex vivo Tissue Model

Abstract: The healthy human epidermis provides physical protection and is impenetrable for pathogenic microbes. Nevertheless, commensal and pathogen bacteria such as Staphylococcus aureus are able to colonize the skin surface, which may subsequently lead to infection. To identify and characterize regulatory elements facilitating adaptation of S. aureus to the human skin environment we used ex vivo tissue explants and quantified S. aureus gene transcription during co-culture. This analysis provided evidence for a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 29 publications
5
19
0
Order By: Relevance
“…Given the low abundance of fibrinogen on human skin, the high expression in toe web spaces could indicate additional, so far uncharacterized functions of s dr G. The high expression of WTA was also demonstrated during nasal colonization of S. aureus ( Burian et al, 2010a , b ). Again, similar to persistent colonization of the human nose ( Burian et al, 2010b ) and early colonization of the skin ( Burian et al, 2021 ) by S. aureus , we observed a strong expression of the autolysin sce D. Interestingly, although sce D was expressed in both niches, it was clearly overrepresented in the nose. This high sce D transcription in both species underscore the importance of the lytic transglycosylase and may therefore be a useful candidate for developing a targeted therapy by inhibition of sce D. Such therapy could play a role especially in atopic dermatitis when massive colonization with S. aureus is responsible for the severity of the disease ( Totte et al, 2016 ) and S. epidermidis also has a deleterious effect by expressing, for example, the protease ecp A ( Cau et al, 2021 ).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Given the low abundance of fibrinogen on human skin, the high expression in toe web spaces could indicate additional, so far uncharacterized functions of s dr G. The high expression of WTA was also demonstrated during nasal colonization of S. aureus ( Burian et al, 2010a , b ). Again, similar to persistent colonization of the human nose ( Burian et al, 2010b ) and early colonization of the skin ( Burian et al, 2021 ) by S. aureus , we observed a strong expression of the autolysin sce D. Interestingly, although sce D was expressed in both niches, it was clearly overrepresented in the nose. This high sce D transcription in both species underscore the importance of the lytic transglycosylase and may therefore be a useful candidate for developing a targeted therapy by inhibition of sce D. Such therapy could play a role especially in atopic dermatitis when massive colonization with S. aureus is responsible for the severity of the disease ( Totte et al, 2016 ) and S. epidermidis also has a deleterious effect by expressing, for example, the protease ecp A ( Cau et al, 2021 ).…”
Section: Discussionsupporting
confidence: 68%
“…Besides PGA, resistance to AMPs is mediated by the expression of dlt A, which leads to the d-alanylation of teichoic acids, thereby reducing the anionic charge of the bacterial surface ( Simanski et al, 2013 ). Since the putative chitinase B (SE0760) is selectively expressed on skin and it is known to mediate skin invasion ( Zhang et al, 2003 ), it would be interesting to investigate in further studies whether a SE0760 mutant is less able to colonize and persist on skin using, for example, our newly established human colonization model ( Burian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that, within 30 min of gentamicin exposure (100× the MIC), there is a significant elevation in the expression of SigB, a stress-responsive alternative sigma factor ( 26 , 27 ). SigB activity positively influences the expression of clumping factors and fibronectin-binding proteins, which could explain the increase in aggregation observed with the gentamicin-treated bacteria ( 28 30 ). Taken together, these findings confirm our speculation that bridging aggregation does occur through the rapid interaction of bacterial adhesins with fibrinogen, but they suggest that it is not the only contributor to the aggregate phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that within 30 minutes of gentamicin exposure (100x the MIC), there is a significant elevation in the expression of SigB- a stress-responsive alternative sigma factor (26),(27). SigB activity positively influences the expression of clumping factors and fibronectin-binding proteins, which could explain the increase in aggregation observed with the gentamicin-treated bacteria (28),(29),(30). Taken together, these findings confirm our speculation that bridging aggregation does occur through the rapid interaction of bacterial adhesins with fibrinogen but suggest that it alone is not the only contributor to the aggregate phenotype.…”
Section: Discussionmentioning
confidence: 99%